Crystal structure of chlorido(2-1-[2-(4-chlorophenyl)hydrazin-1-ylidene-κN]ethylpyridine-κN)(η5-pentamethylcyclopentadienyl)rhodium(III) chloride. (March 2015) - Devika, Neelakandan; Raja, Nandhagopal; Ananthalakshmi, Subbiah; Therrien, Bruno
No abstract available